Beyond Money: Wealth and Wellbeing of the Business Family - Vazquez, Pedro; Campopiano, Giovanna (European Journal of Family Business, 2023)
This article offers a conceptual discussion about the relationship between wealth and wellbeing of the business family. It provides a psychological perspective on ownership that explains the effect of wealth on individual and collective dimensions relevant to business families, namely psychological ownership, socioemotional wealth, and ownership competences. The study provides an integrative framework and offers propositions that illustrate the theoretical and practical implications of the model as regards the relationship between wealth and wellbeing of the business family.